Survey of wild Vigna in southern Africa - Padulosi, S.; Laghettf, G.; Ng, N.Q.; Pienaar, B.; Perrino, P. (1991)
In 1988 collecting and expeditionsto Southern Africa gathered valuable genetic diversity of wild species of Virgna. A remarkable amount of variability is present in the samples of V. Unguiculata (L.) Walp. Collected in Swaziland and the Republic of South Africa. The data collected, together with information gathered on previous collecting expeditions, strongly support the theory that Southern Africa is the centre of origin for section Catjang of this species.